Management and control of air emissions from electronic industries - Bin Babar, Zaeem (2014)
Volatile organic compounds (VOCs) including acetone, dichloromethane, ethanol, ethylene glycol, iso-propyl alcohol, and several other aromatic compounds are emitted during the manufacturing processes in electronic industries. These VOCs pose problems to human health and the environment. Stringent environmental legislations imposed by government agencies on VOCs force electronic industries to adopt effective air pollution-treatment methods. This article provides a detailed review of VOCs that are emitted from different processes in the electronic industry, conventional, and current technologies that are used to remove toxic air pollutants and an innovative application of biotechnology for removal of VOCs from electronic industry.